1991
DOI: 10.1523/jneurosci.11-09-02804.1991
|View full text |Cite
|
Sign up to set email alerts
|

The postsynaptic inhibitory control of lumbar motoneurons during the atonia of active sleep: effect of strychnine on motoneuron properties

Abstract: The present study examined the effects of strychnine on the tonic hyperpolarization and the changes in membrane properties of lumbar motoneurons that occur during active sleep. To carry out these studies, intracellular recordings from lumbar motoneurons were combined with the juxtacellular microiontophoretic application of strychnine in chronic, undrugged, normally respiring cats. During active sleep, compared to quiet sleep, motoneurons that were not exposed to strychnine exhibited tonic hyperpolarization, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 20 publications
2
77
1
5
Order By: Relevance
“…Using intracellular recording and microiontophoretic techniques, Chase and his colleagues found that IPSPs in both cranial and spinal motoneurons can be blocked by application of strychnine, a glycine antagonist, during natural (Chirwa et al, 1991;Soja et al, 1991) and pontine carbachol-induced (Kohlmeier et al, 1996;Yamuy et al, 1999) REM sleep in the cat. GABA has also been shown to inhibit motoneuron activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using intracellular recording and microiontophoretic techniques, Chase and his colleagues found that IPSPs in both cranial and spinal motoneurons can be blocked by application of strychnine, a glycine antagonist, during natural (Chirwa et al, 1991;Soja et al, 1991) and pontine carbachol-induced (Kohlmeier et al, 1996;Yamuy et al, 1999) REM sleep in the cat. GABA has also been shown to inhibit motoneuron activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, by means of intracellular recordings during PS, it has been shown that trigeminal, hypoglossal and spinal motoneurons are tonically hyperpolarized by large inhibitory postsynaptic potentials (IPSPs) during PS. Further when these recordings were combined with local iontophoretic application of strychnine (a specific antagonist of the inhibitory neurotransmitter, glycine), motoneurons hyperpolarization was strongly decreased indicating that they are tonically inhibited by glycinergic neurons during PS [12][13][14]. It has then been shown that the levels of glycine but also that of GABA increase within hypoglossal and spinal motor pools during PS-like atonia suggesting that GABA in addition to glycine might contribute to motoneurons hyperpolarization during PS [15].…”
Section: Paradoxical (Rem) Sleep Generating Neurons: the Switch From mentioning
confidence: 99%
“…Another key issue our data addresses is whether active sleep-specific suppression of the sciatic nerve-evoked responses in DSCT neurons can be adequately explained by withdrawal of afferent input, i.e., disfacilitation, that is secondary to motor atonia and the hyperpolarization of motoneurons (Chase et al 1989;Morales and Chase 1981;Soja et al 1991). Disfacilitation is unlikely to account for the reduced synaptic responses in this study because sciatic nerve stimulation bypasses peripheral sensory receptors.…”
Section: State-dependent Suppression Of Sciatic Nerveevoked Responsesmentioning
confidence: 86%
“…Lumbar motoneurons are known to be tonically hyperpolarized during non-eye movement periods of active sleep by a process of glycine-mediated postsynaptic inhibition (Chase et al 1989;Soja et al 1991). The amplitude of monosynaptic EPSPs intracellularly recorded from motoneurons decreases during non-eye movement periods of active sleep compared with quiet sleep.…”
Section: State-dependent Suppression Of Sciatic Nerveevoked Responsesmentioning
confidence: 99%
See 1 more Smart Citation